2018 IEEE 5th International Workshop on Evolving Security &Amp; Privacy Requirements Engineering (ESPRE) 2018
DOI: 10.1109/espre.2018.00010
|View full text |Cite
|
Sign up to set email alerts
|

Tool-Supporting Data Protection Impact Assessments with CAIRIS

Abstract: The General Data Protection Regulation (GDPR) encourages the use of Data Protection Impact Assessments (DPIAs) to integrate privacy into organisations' activities and practices from early design onwards. To date, however, there has been little prescription about how Security & Privacy Requirements Engineering processes map to the necessary activities of a DPIA, and how these activities can be tool-supported. To address this problem, we present a tool-supported process for undertaking DPIAs using existing Requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…A sub-set of the IRIS concepts relevant to this paper is provided in Figure 1. Coles et al [2] demonstrated how use cases and assets provide the concepts necessary to threat model with data flow diagrams, and how -in addition to modelling system goals -the KAOS modelling language [12] is also suitable for modelling attack trees as obstacles. To make attacker assumptions more explicit, IRIS supports the specification of attackers.…”
Section: Security and Software Design Meta-modelsmentioning
confidence: 99%
“…A sub-set of the IRIS concepts relevant to this paper is provided in Figure 1. Coles et al [2] demonstrated how use cases and assets provide the concepts necessary to threat model with data flow diagrams, and how -in addition to modelling system goals -the KAOS modelling language [12] is also suitable for modelling attack trees as obstacles. To make attacker assumptions more explicit, IRIS supports the specification of attackers.…”
Section: Security and Software Design Meta-modelsmentioning
confidence: 99%
“…11 DPIAs should be relatively cheap to implement with sufficient resources and tools. 12 However, while there is advice on the legal requirements for DPIA and the elements of what practitioners should do to undertake a DPIA there has been little prescription about how security and privacy requirements engineering processes map to the necessary activities of a DPIA, and how these activities can be toolsupported. 12 Coles, Fairy and Ki-Aries have studied existing privacy requirements engineering approaches and tools that support carrying out DPIAs.…”
Section: Data Protection Impact Assessmentmentioning
confidence: 99%
“…12 However, while there is advice on the legal requirements for DPIA and the elements of what practitioners should do to undertake a DPIA there has been little prescription about how security and privacy requirements engineering processes map to the necessary activities of a DPIA, and how these activities can be toolsupported. 12 Coles, Fairy and Ki-Aries have studied existing privacy requirements engineering approaches and tools that support carrying out DPIAs. 12 The existing approaches capture the elements that would be needed by a DPIA, but two barriers need to be overcome before such approaches are ready for security and practitioners to use in DPIAs: 12 1) more prescription is needed to indicate what tools and techniques map to different stages of a DPIA, and 2) such steps need to be adequately tool-supported, such that data input in one step can be used to support reasoning and analysis in others.…”
Section: Data Protection Impact Assessmentmentioning
confidence: 99%
See 2 more Smart Citations